Nematodes from galls on Myrtaceae. VII. Fergusobia from ‘leafy’ leaf bud galls in Australia, with re-description of Fergusobia tumifaciens (Currie 1937) Wachek 1955 and descriptions of Fergusobia planchonianae n. sp. and Fergusobia viminalisae n. sp. - Davies, Kerrie A.; Ye, Weimin; Giblin-Davis, Robin M.; Taylor, Gary S.; Hodda, Mike; Thomas, W. Kelley (Zootaxa, 2014)
Fergusobia tumifaciens (Currie 1937) Wachek 1955, the type species for the genus Fergusobia, is re-described from specimens collected from ‘leafy’ leaf bud galls on Eucalyptus bridgesiana near Albury in New South Wales, Australia. It is morphologically characterized by the combination of an open C-shaped parthenogenetic female with a small broadly conoid tail, a C-shaped infective female with a bluntly rounded tail tip, and an arcuate to J-shaped male with angular spicules, not heavily sclerotised, and short to mid-length peloderan bursa. Two new species of Fergusobia, collected from ‘leafy’ leaf bud galls on, respectively, Eucalyptus planchoniana in Queensland, and E. viminalis in South Australia, Australia, are described. Fergusobia planchonianae Davies n. sp. is characterised by the combination of a C-shaped parthenogenetic female with a conoid tail, an arcuate infective female with an hemispherical tail tip, and an almost straight to arcuate to C-shaped male with an angular spicule, a long peloderan bursa and a narrow tail. Fergusobia viminalisae Davies n. sp. is characterised by the combination of an open C-shaped parthenogenetic female with a broadly conoid tail, a C-shaped infective female with a bluntly rounded tail tip, and an arcuate to J-shaped male with an angular (not heavily sclerotised) spicule and short to mid-length peloderan bursa. The shield morphologies of the fly larvae associated with the ‘leafy’ leaf bud galls and their possible relationships are outlined. Possible evolutionary relationships of the Fergusobia nematodes from these galls are discussed, considering their morphology, DNA sequences, and the relationships of the associated Fergusonina flies and host plants.